Action of formulated rosemary against Meloidogyne incognita in soybean - Cazzo, Victor Natan; Stangarlin, José Renato; Mattei, Danielle; Kuhn, Odair José; Cavilia Junior, Fortunato; Lorenzetti, Eloisa (Scientia Agraria Paranaensis, 2020)
The damage caused by nematodes has been severe in many crops in Brazil, causing a reduction in agricultural yield. The objective of this work was to evaluate the efficiency of a formulation, elaborated with extract of the rosemary (Rosmarinus officinalis) and cassava bark, on the control of nematode Meloidogyne incognita in soybean. The doses evaluated were 0.0; 25; 50; 100; 150 and 200 mL of the dried formulation per pot of 3 L containing soybean plants. The experiment was conducted in a greenhouse, in a randomized block design, with five replications. We evaluated dried and fresh masses of aerial part, fresh mass of root, and the number of egg mass, galls and second stage juveniles (J2) and eggs in root and soil. The soybean plants showed growth reduction resulting from the interaction of the formulation, maybe due a phytotoxic effect from cassava bark. There was allelopathic effect in soybean plants treated with formulated made with cassava bark + aqueous extract of rosemary, evidenced by inhibition in plant development according to the increase in doses of the formulated. Moreover, the formulated was not efficient in the control and or reduction of M. incognita.